Sula's voyage - Torres, Catherine (Singapore : Scholastic Inc., 2016)
"Fifteen-year-old Sula has always known she is different. Even though her parents have shown her nothing but love and acceptance, she sees her dark skin as reminder of how she doesn't fit in with the rest of her family. What's worse is she also feels that her parents are hiding something from her. After getting expelled from school, Sula reluctantly goes to stay with her mother's friends. There she unexpectedly finds herself on a journey of self-discovery - a journey that keeps drawing her to the sea. Sula must not only figure out her parents' secret, but also just how different, and possibly magical, she really is."
Asian book award finalist
Keywords: Families -- Fiction; Parent and child -- Fiction; Families